2013
DOI: 10.1183/09031936.00058713
|View full text |Cite|
|
Sign up to set email alerts
|

Adrenomedullin refines mortality prediction by the BODE index in COPD: the "BODE-A" index

Abstract: The BODE (body mass index, airflow obstruction, dyspnoea, exercise capacity) index is wellvalidated for mortality prediction in chronic obstructive pulmonary disease (COPD). Concentrations of plasma pro-adrenomedullin, a surrogate for mature adrenomedullin, independently predicted 2-year mortality among inpatients with COPD exacerbation.We compared accuracy of initial pro-adrenomedullin level, BODE and BODE components, alone or combined, in predicting 1-year or 2-year all-cause mortality in a multicentre, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…Additionally, recent observational studies demonstrated that in patients during or just recovering from COPD exacerbation [39][40][41] or in patients with stable COPD [40,42], ProADM is a powerful independent prognosticator of long-term non-survival [39][40][41][42]. Some of this work also shows that when combined with demographic and clinical variables, ProADM provides significant incremental mortality prediction accuracy [41,42].…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Additionally, recent observational studies demonstrated that in patients during or just recovering from COPD exacerbation [39][40][41] or in patients with stable COPD [40,42], ProADM is a powerful independent prognosticator of long-term non-survival [39][40][41][42]. Some of this work also shows that when combined with demographic and clinical variables, ProADM provides significant incremental mortality prediction accuracy [41,42].…”
Section: Introductionmentioning
confidence: 70%
“…Some of this work also shows that when combined with demographic and clinical variables, ProADM provides significant incremental mortality prediction accuracy [41,42]. Additional data [43][44][45] suggest that ProADM may be a global cardiopulmonary stress marker [45].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations